2016
DOI: 10.1016/j.bbabio.2016.03.018
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial reactive oxygen species: Do they extend or shorten animal lifespan?

Abstract: Testing the predictions of the Mitochondrial Free Radical Theory of Ageing (MFRTA) has provided a deep understanding of the role of reactive oxygen species (ROS) and mitochondria in the aging process. However those data, which support MFRTA are in the majority correlative (e.g. increasing oxidative damage with age). In contrast the majority of direct experimental data contradict MFRTA (e.g. changes in ROS levels do not alter longevity as expected). Unfortunately, in the past, ROS measurements have mainly been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
82
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 91 publications
(83 citation statements)
references
References 162 publications
(210 reference statements)
1
82
0
Order By: Relevance
“…Among these inflammatory cells, phagocytes such as neutrophils and mononuclear phagocytes can also be recruited and produce ROS to kill the pathogens during the so-called “respiration burst” [28]. However, ROS are not just helpful weapons of phagocytes but are harmful agents causing oxidative stress and damage nearby cells and molecules at exorbitant concentration [29]. …”
Section: Discussionmentioning
confidence: 99%
“…Among these inflammatory cells, phagocytes such as neutrophils and mononuclear phagocytes can also be recruited and produce ROS to kill the pathogens during the so-called “respiration burst” [28]. However, ROS are not just helpful weapons of phagocytes but are harmful agents causing oxidative stress and damage nearby cells and molecules at exorbitant concentration [29]. …”
Section: Discussionmentioning
confidence: 99%
“…In this study, H 2 O 2 exposure induced oxidative stress evidenced by decreased cell viability, inhibited T-AOC, and increased leakage of LDH, while NAC treatment markedly improved antioxidant system. Mitochondria are the powerhouses of the cell, producing a considerable share of cellular ATP and playing a central role in cellular function and metabolism [28]. Our previous report showed that mitochondrial dysfunction was observed with decrease in the basal respiration, maximal respiration, and nonmitochondrial respiration after LPS treatment [1].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, mice deleted for the gene of the p66shc adaptor protein have reduced ROS generation and delayed aging (Migliaccio et al., 1999; Napoli et al., 2003). However, new recent data challenged this hypothesis as they show that ROS can be beneficial and extend lifespan at least in lower organisms such as flies and worms (Sanz, 2016; Sena & Chandel, 2012). Accumulating evidence suggests that other aspects of mitochondrial physiology must be considered to explain the contribution of mitochondria to aging (Gonzalez‐Freire et al., 2015; Payne & Chinnery, 2015).…”
Section: Regulating Factors Of Mptp and Agingmentioning
confidence: 99%